Making the weight: A case study from professional boxing - Morton, J. P.; Robertson, C.; Sutton, L.; MacLaren, D. P. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
Professional boxing is a combat sport categorized into a series of weight classes. Given the sport`s underpinning culture, boxers` typical approach to "making weight" is usually via severe acute and/or chronic energy restriction and dehydration. Such practices have implications for physical performance and also carry health risks. This article provides a case-study account outlining a more structured and gradual approach to helping a professional male boxer make weight for the 59-kg superfeatherweight division. Over a 12-week period, the client athlete adhered to a daily diet approximately equivalent to his resting metabolic rate (6-7 MJ; 40% carbohydrate, 38% protein, 22% fat). Average body-mass loss was 0.9 ± 0.4 kg/wk, equating to a total loss of 9.4 kg. This weight loss resulted in a decrease in percent body fat from 12.1% to 7.0%. In the 30 hr between weigh-in and competition, the client consumed a high-carbohydrate diet (12 g/kg body mass) supported by appropriate hydration strategies and subsequently entered the ring at a fighting weight of 63.2 kg. This nutritional strategy represented a major change in the client`s habitual weight-making practices and did not rely on any form of intended dehydration during the training period or before weighing in. The intervention demonstrates that a more gradual approach to making weight in professional boxing can be successfully achieved via a combination of restricted energy intake and increased energy expenditure, providing there is willingness on the part of the athlete and coaches involved to adopt novel practices.